2019
DOI: 10.1182/blood-2018-09-873984
|View full text |Cite
|
Sign up to set email alerts
|

Human megakaryocytes possess intrinsic antiviral immunity through regulated induction of IFITM3

Abstract: Evolving evidence indicates that platelets and megakaryocytes (MKs) have unexpected activities in inflammation and infection; whether viral infections upregulate biologically active, antiviral immune genes in platelets and MKs is unknown, however. We examined antiviral immune genes in these cells in dengue and influenza infections, viruses that are global public health threats. Using complementary biochemical, pharmacological, and genetic approaches, we examined the regulation and function of interferon-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
170
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 70 publications
12
170
0
1
Order By: Relevance
“…Dengue virus can infect megakaryocytes, 47 and megakaryocytes can upregulate type-I interferon genes in response to dengue and influenza viruses. 48 While dengue virus can replicate in platelets, 49 influenza virus can be internalized by platelets and is transported through the circulatory system in humans. 50 , 51 Influenza virus-induced lung injury in mice can be prevented by targeting of platelet αIIbβ3 by an antagonist or other antiplatelet compounds such as clopidogrel, an antagonist of ADP (adenosine diphosphate) receptors, or blockers of protease-activated receptor-4, thus pointing to an active role by platelets in influenza pathogenesis.…”
mentioning
confidence: 99%
“…Dengue virus can infect megakaryocytes, 47 and megakaryocytes can upregulate type-I interferon genes in response to dengue and influenza viruses. 48 While dengue virus can replicate in platelets, 49 influenza virus can be internalized by platelets and is transported through the circulatory system in humans. 50 , 51 Influenza virus-induced lung injury in mice can be prevented by targeting of platelet αIIbβ3 by an antagonist or other antiplatelet compounds such as clopidogrel, an antagonist of ADP (adenosine diphosphate) receptors, or blockers of protease-activated receptor-4, thus pointing to an active role by platelets in influenza pathogenesis.…”
mentioning
confidence: 99%
“…Intriguingly, we found that the hemostasis gene signature was able to further distinguish critical from severe COVID-19 patients, underlying the hypothesis that deregulated hemostasis, in a continuum with in ammation, could drive COVID-19 progression into critical disease. Viral infection and sepsis models have been associated with platelet gene expression and functional alterations (35,36). However, some unique features may characterize SARS-CoV-2-mediated platelet dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a shift in platelet-lymphocyte ratio may indicate the occurrence of an acute inflammatory or thrombotic event and therefore have prognostic value (Qu et al, 2020). Thus, thrombocytopaenia may reflect (a) alteration in thrombopoiesis due to the bone marrow or lungs (and potentially spleen) being inflamed or receiving inflammatory and trauma-related thrombopoietic cues; (b) localised lung recruitment of platelets as a facet of their role in the immune response or alveolar coagulation; (c) disseminated intravascular coagulation (DIC) throughout the body (Xu, Zhou, & Xu, 2020); or (d) platelet-viral interaction, although this remains hypothetical as an engagement of platelets with SARS-CoV-2 has not been described (Amgalan & Othman, 2020 Results of studies in mice modelling influenza agree on the necessity for platelets in the immune response and inflammation but conflict as to whether this is beneficial (Campbell et al, 2019;Guo et al, 2017), or detrimental (Boilard et al, 2014;Lê et al, 2015). Additionally, platelets respond to influenza virus by increasing complement availability and encourage the release of NETs into blood, and so platelets may be important integrators linking viral infection to neutrophil responses that are associated with coagulopathy and venous thrombosis (Koupenova et al, 2019).…”
Section: Platelet Responses Coagulopathy and Hyperinflammationmentioning
confidence: 99%